Specific Real-Time PCR Assay Targeting D-loop Gene and Short Amplicon Sequencing for Identification of Monkey Meat in Beef Meatballs - Dwiky Ramadhani Kurniawati; Sismindari Sismindari; Rumiyati Rumiyati; Fajar Setyo Wibowo; Ni Wayan Pebriyanti; Irnawati Irnawati; Abdul Rohman (Universitas Gadjah Mada, 2024)
Macaque monkey (Macaca fascicularis) meat (MM) has been reported to be consumed as meatball and soup products in Indonesia. MM is not allowed to be traded in Indonesia and is considered not halal meat; therefore, MM is not allowed to be consumed by Muslim communities. In this study, species-specific primer (SSP) targeting on mitochondrial displacement (D-loop) region coupled with real-time PCR assay was used to identify monkey meat in beef meatballs. The PCR product was also subjected to sequencing in order to ensure the adulteration practice of MM in beef meatballs. The primers were designed and subjected to in silico specificity test using BLAST. The used primers were: forward: 5’-TGACTCCCACCACATCCC-3’ and reverse: 5’-GTGTGGAGCTAGAATATTGAACCG-3’. Real-time PCR assay using SSP targeting on mt-D-loop primers was capable of identifying MM in meatball products, specifically with a detection limit of 0.0078 ng corresponding to 1% MM in beef meatballs. The developed method can be proposed as the standard method for detecting MM in food products intended for halal authentication analysis, provided that DNAs are available in food products.